2013
DOI: 10.1590/s0100-72032013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre o nível de atividade física e a incidência da síndrome pré-menstrual

Abstract: ResumoOBJETIVO: Verificar a relação entre o nível de atividade física e a incidência da síndrome pré-menstrual. MÉTODOS: Trata-se de um estudo transversal realizado com 71 universitárias aparentemente saudáveis (24,4±4,8 anos; 61,5±8,7 kg; 1,63±0,06 m). O nível de atividade física foi mensurado através de questionário, e a síndrome pré-menstrual foi verificada através de um diário de sintomas respondido durante dois ciclos menstruais consecutivos. No diário são considerados 17 sintomas, os quais deveriam ser p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
1
10
1
6
Order By: Relevance
“…Identifying modifiable risk factors, such as physical activity, is important to help improve premenstrual symptom severity in women who may not need or want a pharmacological remedy. However, unlike some prior studies [8,1115,17,18], we did not find a lower prevalence of PMS or premenstrual symptoms in women who participated in high levels of physical activity compared to women who participated in lower levels or no physical activity. We also did not find that a relationship between physical activity and PMS was confounded by BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…Identifying modifiable risk factors, such as physical activity, is important to help improve premenstrual symptom severity in women who may not need or want a pharmacological remedy. However, unlike some prior studies [8,1115,17,18], we did not find a lower prevalence of PMS or premenstrual symptoms in women who participated in high levels of physical activity compared to women who participated in lower levels or no physical activity. We also did not find that a relationship between physical activity and PMS was confounded by BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…Women diagnosed with PMS had a lower level of physical activity than healthy women. These results show that the practice of physical exercise can help with the prevention and/or treatment of PMS [27]. A similar result was found in the present study, with a higher intake of lipids by sedentary PMS women in the premenstrual period.…”
Section: Discussionsupporting
confidence: 92%
“…In a survey of 71 universities in the city of Juiz de Fora, Teixeira & Oliveira [3] tested the hypothesis of a correlation between the physical activity level (PAL) and the symptoms of PMS. They found that the more prevalent premenstrual symptoms were: nervous tension, irritability, crying, insomnia, anxiety, change in mood, headache and fatigue.…”
Section: Discussionmentioning
confidence: 99%